The Implementation of Learning Quality Management in Increasing Graduates Quality - Soewita, Daud; Syamsudin, Abin; Gintings, Abdorrakhman; Iriantara, H. Yousal (Advances in Social Sciences Research Journal, 2020)
This research aims to describe the implementation of planning, organizing, learning execution, and evaluation of learning outcomes based on information and computer technology at SMAN 5, SMK N 10, SMAN N 11 of Tangerang Regency. The programs to improve the learning quality in these 3 high schools were conducted continuously through programs of enhancing the teachers’ competency based on information and communication technology (ICT). Teachers as educators generally have interesting ideas and innovations in teaching by implementing ICT when compiling, executing, and evaluating learning outcomes. ICT-based learning seemed more dynamic, interactive, flexible, and interesting for the students. Educators searched for strategies in teaching-learning process by deploying inspiring techniques for the talented students. The students interested with the learning materials could interact with the teachers intensively, not only at the learning time. The quality management of technology-based education was a profound learning for the educators and education staff. This was because they acquired knowledge and understanding in planning, organizing, directing, and controlling the sources of education in order to effectively, efficiently, autonomously achieve the education targets and to produce quality they were proud of.